Information Access Skills in Mothers as Containment of Internet Negative Impact - Limilia, Putri; P., Benazir Bona (Universitas Semarang, 2018)
Media and Information Literacy (MIL) skills was one of the skills that must be possessed by netizens. These skills become important in the effort of coping with the negative impact of the internet. The high penetration of the internet is not followed by the high skill of MIL. Therefore, the writers are interested to know the skills of information and media literacy (access skills) in mothers. This study uses descriptive quantitative method by using questionnaires as means of data collection. The result of the study shows that mothers tend to have moderate-level information access skills. The skills are reflected in the skills of mothers at moderate level in understanding the role of information, seeking sources of information, accessing information effectively and efficiently, and storing information.